2018
DOI: 10.5114/pm.2018.74901
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction prevalence in a group of pre- and postmenopausal Mexican women

Abstract: IntroductionTo determine the prevalence of sexual dysfunction in pre and postmenopausal women.Material and methodsA cross-sectional, descriptive, comparative study was done in climacteric women from 40 to 59 years of age. Female sexual function was evaluated with the female sexual function index (FSFI) on the day of consultation. The comparison between pre and postmenopausal women and between those with or without sexual dysfunction was done with Mann Whitney U test, χ2, and Spearman’s correlation analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…In the present study, the most highly rated aspect of female sexual function was satisfaction, while arousal and excitation obtained the lowest average scores. These findings are in agreement with the results of previous studies [ 30 , 31 ]. The mean ± standard deviation for the FSFI total score was 18.22 ± 10.60, which is similar to reports made by Jamali et al [ 32 ] for postmenopausal Iranian women (60.10 ± 6.89 years), and by Gozuyesil et al [ 33 ] (18.8 ± 8.7).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, the most highly rated aspect of female sexual function was satisfaction, while arousal and excitation obtained the lowest average scores. These findings are in agreement with the results of previous studies [ 30 , 31 ]. The mean ± standard deviation for the FSFI total score was 18.22 ± 10.60, which is similar to reports made by Jamali et al [ 32 ] for postmenopausal Iranian women (60.10 ± 6.89 years), and by Gozuyesil et al [ 33 ] (18.8 ± 8.7).…”
Section: Discussionsupporting
confidence: 94%
“…However, we must bear in mind that the latter assessed sexual function only among Turkish women aged 40–60. Be that as it may, the mean FSFI total score was higher in other studies dealing with subjects of similar mean age, such as those by Carranza-Lira et al [ 31 ] (with a score of 22) or Zhang et al [ 34 ] (21.52 ± 2.85), after assessing Mexican and Chinese women, respectively. The differences may be due to the specific culture or the mean age of the participants.…”
Section: Discussionmentioning
confidence: 68%
“…Age was found to negatively correlate with the female sexual function index (FSFI) score (ρ = −0.324, p-value < 0.001). 11 The prevalence of sexual dysfunction was significantly higher among the study group than in the control group. The study also found that with an increase in blood glucose (HbA1c) levels, body mass index (BMI), and duration of diabetes, the prevalence of sexual dysfunction also increased.…”
Section: Introductionmentioning
confidence: 75%
“…However, 45% of middle-aged women have sexual problems, and 15% have a sexual problem that causes them significant personal distress. All of this can have an adverse impact on both physical and psychological health 43 …”
Section: Discussionmentioning
confidence: 99%